Estimates of the prevalence of undiagnosed HIV among children living with HIV in Eswatini, Lesotho, Malawi, Namibia, Tanzania, Zambia, and Zimbabwe from 2015 to 2017: an analysis of data from the cross-sectional Population-based HIV Impact Assessment surveys. Issue 2 (February 2022) - Teasdale, Chloe A; Zimba, Rebecca; Abrams, Elaine J; Sachathep, Karampreet; Ndagije, Felix; Nuwagaba-Biribonwoha, Harriet; Musuka, Godfrey; Mugurungi, Owen; Maile, Limpho; Mahy, Mary; Low, Andrea
Summary: Background: In 2020, there were an estimated 1·7 million children younger than 15 years living with HIV worldwide, but there are few data on the proportion of children living with HIV who are undiagnosed. We aimed to estimate the prevalence of undiagnosed HIV among children living with HIV in Eswatini, Lesotho, Malawi, Namibia, Tanzania, Zambia, and Zimbabwe. Methods: We conducted an analysis of data from the cross-sectional Population-based HIV Impact Assessment (PHIA) surveys from 2015 to 2017. PHIAs are nationally representative surveys measuring HIV outcomes. HIV rapid test data (with PCR confirmatory testing for children aged <18 months) were used to measure HIV prevalence among children in each country (Eswatini, Lesotho, Malawi, Namibia, Tanzania, Zambia, and Zimbabwe). Mothers or guardians reported previous HIV testing of children and previous results. Detection of antiretroviral medications was done using dried blood spots. Children who tested positive in the PHIA with previous negative or unknown HIV test results and without detectable antiretroviral medication blood concentrations were considered previously undiagnosed; all other children who tested positive were considered previously diagnosed. Survey weights with jackknife variance were used to generate national estimates of HIV prevalence and undiagnosed HIV in children aged 1–14 years. We also report the prevalence (weighted proportions) of antiretroviral therapy coverage and viral load suppression (<400 copies per mL). Findings: Between 2015 and 2017, 42 248 children aged 1–14 years were included in the surveys, of whom 594 were living with HIV. Across the seven countries, the estimated weighted HIV prevalence was 0·9% (probability band 0·7–1·1) and we estimated that there were 425 000 (probability band 365 000–485 000) children living with HIV. Among all children living with HIV, 61·0% (n=259 000 [probability band 216 000–303 000]) were previously diagnosed and 39·0% (n=166 000 [128 000–204 000]) had not been previously diagnosed with HIV. Among previously diagnosed children living with HIV, 88·4% had detectable antiretroviral medication blood concentrations and 48·3% had viral load suppression. Among all children living with HIV (regardless of previous diagnosis status), 54·7% had detectable antiretroviral medication blood concentrations and 32·6% had viral load suppression. Interpretation: Our findings show the uneven coverage of paediatric HIV testing across these seven countries and underscore the urgent need to address gaps in diagnosis and treatment for all children living with HIV. Funding: None.